Analisis Pengaruh Pelatihan Karyawan terhadap Kinerja Karyawan PT. Bento Group Indonesia (Bento Kopi) Cabang Kota Cimahi - Ayu Virgiayani Fazri; Ida Jalilah Fitria (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
Today's globalization is characterized by increasing intensity of competition among companies and technological advances that pose challenges for companies in managing various aspects. Faced with change and competition at both the national and international levels, employees must be prepared to adapt to technology, such as the emergence of new telecommunications or new working methods undertaken. The achievement of the purpose of the company is due to the human effort in planning, organizing, directing, coordinating and controlling operational activities. Trained human resources influence the performance and responsibility of the company as a whole. The objective of this survey is to find out (1) the impact of employment training on employee performance in employees of Bento Kopi Branch Cimahi PT. Bento Group Indonesia and, (2) the correlation of employee training to the performance of employees in Bento Kopi Branch Cimahi. The research methodology uses qualitative descriptive approaches, data collection using obreservation, interviews and library studies. Based on the results of observations and interviews with employees of Bento Kopi Branch Cimahi this obtained quite good results on the training work carried out by the entire employees. The performance of employees of Bento Kopi Branch Cimahi has increased after a period of regular work training carried out by the company. With the presence of this work training affects the ability of employees to complete their tasks and responsibilities well and maximum.